PENGARUH KELOMPOK REFERENSI DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KFC METROPOLITAN CITY PEKANBARU - Fadilah, Hefni; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at KFC Metropolitan City Pekanbaru, located on jalan H.R Soebrantas, Km. 12.5, Tampan, Metropolitan City Pekanbaru-Riau. The problem in this study is the decline and failure to reach the target number of customers and income that is thought to be influenced by consumer purchasing decisions. The purpose of this study was to determine the effect of reference groups and pricing on consumer purchasing decisions at KFC Metropolitan City Pekanbaru. Samples are taken based on the method using the Slovin formula, amounting to 100 respondents. Hypothesis testing uses a simple linear regression analysis method and multiple linear regression analysis with the results showing that the reference group and price setting significantly influence consumer purchasing decisions at KFC Metropolitan City Pekanbaru. With a simple linear regression calculation the coefficient of determination (R2) of the reference group on consumer purchasing decisions obtained R Square of 0.258 or 25.8%, pricing for consumer purchasing decisions obtained R Square of 0.303 or 30.3% and calculation of multiple linear regression coefficient of determination (R2) the reference group and pricing for consumer purchasing decisions obtained R Square of 0.414 or 41.4%. This shows that the reference group and price setting influence 41.4% of consumer purchasing decisions at KFC Metropolitan City Pekanbaru. While the remaining 58.6% is influenced by other variables not examined in this study. Keywords : Reference Group, Pricing, Consumer Purchasing Decisions